2018
DOI: 10.3920/bm2017.0152
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota characterisation in obese patients before and after bariatric surgery

Abstract: Intestinal microbiota analysis of obese patients after bariatric surgery showed that Proteobacteria decreased after laparoscopic sleeve gastrectomy (SG), while it increased after laparoscopic gastric bypass (LGB). Comparing to normal weight (NW) patients, obese patients that were selected for SG showed an almost equal amount of Firmicutes and Bacteroidetes and the ratio was not affected by the surgery. Obese patients before LGB showed a predominance of Bacteroidetes, whose amount regained a relative abundance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 23 publications
2
30
0
4
Order By: Relevance
“…Thirty articles were categorized into group 1 (BS and microbiota in humans). The work by Campisciano et al [ 37 , 38 ] is included as two original articles, but discussed and summarized as one due to presenting identical results. Twenty-five articles were categorized into group 2 (BS and microbiota in other vertebrates) and four articles were categorized into group 3 (BS and probiotics).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty articles were categorized into group 1 (BS and microbiota in humans). The work by Campisciano et al [ 37 , 38 ] is included as two original articles, but discussed and summarized as one due to presenting identical results. Twenty-five articles were categorized into group 2 (BS and microbiota in other vertebrates) and four articles were categorized into group 3 (BS and probiotics).…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 59 studies, 36 studies applied a pre-post design (baseline measurements provided) (Group 1: n = 23 [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]; Group 2: n = 10 [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]; Group 3: n = 4 [ 70 , 71 , 72 , 73 ]). Sixteen studies used a cross-sectional design (Group 1: n = 6 [ 74 , 75 , 76 , 77 , 78 , 79 ]; Group 2: n = 10 [ 80 , 81 , 82 , 83 , 84 , 85 , 86 ,…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analysis showed that it may be useful in the short term in patients having undergone RYGB or OAGB, but no long-term benefits have been found in RCTs till date. Compared with SG, the composition of gut microbiota was dramatically altered in patients having undergone gastric bypass [34]. We speculate that microecological preparations improved the gut microbiota ecosystem and increased weight loss.…”
Section: Discussionmentioning
confidence: 86%
“…[10] Following bariatric surgery, increased gut microbial diversity and gene richness have been reported. [20][21][22][23][24][25] While the connection between the gut microbiome and sarcoidosis is developing, their relationship may have contributed to the resolution of sarcoidosis following bariatric surgery reported here.…”
Section: Discussionmentioning
confidence: 99%